Pengaruh Kompetensi, Kedisiplinan dan Motivasi Terhadap Kinerja Karyawan - suryanto suryanto (Direktorat Penelitian dan Pengabdian Masyarakat (DPPM) Universitas Pelita Bangsa, 2020)
ABSTRACT The purpose of this study was to analyze the influence of competence, discipline, and motivation on employee performance at the Hermina Hospital Group. The method used with the sampling technique in this study is nonprobability sampling. In determining the number of samples, the Slovin formula, in order to obtain a sample of 108 respondents. The analytical tool used is multiple linear regression. With the following results: Y = - 2.537 + 0.177X1 + 0.1618X2 + 0.9968X3 where X1 is Competence, X2 is Discipline, and X3 is Motivation. The results of this study indicate that competence, discipline and motivation have a significant positive effect on employee performance Hermina Hospital Group. The coefficient of determination R Square value is 0.879 or equal to 87.9%. It means that the competency, discipline, and motivation variables affect employee performance by 87.9%. and the remaining 12.1% is influenced by other variables outside of this study. The suggestion from this research is that to improve employee performance, it is necessary to increase the competence, discipline, and motivation of employees at the Hermina Hospital Group. Keywords : Competence, Discipline, Motivation, and employee performance